قضية خلق القرآن عند الجبرية والمعتزلة وأهل السنة : (دراسة مقارنة نقدية) - Amir Sahidin; Abdul Rohman (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2021)
The discussion of khalqul qur'an is a very crucial issue among the Mutakallimin. The Jabariyyah and Mu'tazilah groups say that the Qur'an is a creature in order to purify Allah from human-like characteristics. In fact, saying khalqul qur'an (the Qur'an is a creature) is the same as negating the nature of God, in the form of kalam. Belief like this will lead to three imperatives: first, as if God as the essence of the nature is a creature. Second, Allah is a mute Rabb, while being mute is a deficiency trait. Third, Allah's knowledge is a creature, because the Qur'an is His knowledge, then how could Allah have created knowledge first in order to have knowledge. Therefore the scholars of the Ahli Sunnah are unanimously agreed that the Qur'an is kalamullah. Among the scholars of the Ahli Sunnah who are very firm in defending the beliefs of the Sunnah are Imam Ahmad bin Hanbal. He not only gave strong arguments, but also refuted the group that said khalqul qur'an with a solid rebuttal. Based on a qualitative method and a comparative critical approach, it was found that, first, Jabariyyah and Mu'tazilah agreed that the Qur'an was a creature. Second, the Sunnah experts in general and Imam Ahmad bin Hanbal in particular insist that the Qur'an is the kalamullah. Third, when their arguments are found, the strongest is the opinion of the Ahli Sunnah. The basis for this difference of opinion is based on their beliefs about the nature of Allah.